Enhancing energy security through efficient decarbonization: Impact of China’s “Constructing Large Units and Restricting Small Ones” policy on thermal power productivity - Jinsong Zhao; Chin-Hsien Yu; Xinghao Li (Chinese Journal of Population, Resources and Environment)
Developing low-carbon and efficient power systems is critical for energy security in the global warming context. We address this issue by focusing on the productivity impact of a decarbonization policy in China’s thermal power sector—namely, the “Constructing Large Units and Restricting Small Ones” (CLRS) initiative. Utilizing a resource misallocation model, we construct a new theoretical framework to distinguish between technical and allocative efficiency and analyze productivity using plant-level data. The results indicate that the CLRS policy has significantly improved the allocative and technical efficiency of China’s coal-fired power sector, thereby ensuring power security. The closure of outdated and highly distorted small coal-fired units, which have been replaced by technologically advanced large units, primarily drives the enhanced efficiency. The policy’s effects are most pronounced in large-scale power plants and those with high coal combustion efficiency. Furthermore, a comparison of power plants’ productivity distribution before and after policy implementation reveals that the CLRS policy not only enhances capital productivity in the coal-fired power sector but also increases rational labor allocation. Our findings have important policy implications for developing countries vis-à-vis building efficient and stable power systems amid climate change.